(untitled) (Italian Journal of Public Health, 2011)
Background: Inequalities in reproductive and child health (RCH) exist, in general, in different regions of India. The present study aims to investigate the current status of RCH and examine the factors responsible for it in different parts of India. Methods: This study utilized data obtained from two Indian studies – (i) National Family Health Survey – 3 (NFHS- 2005-06) and (ii) District Level Household Survey (DLHS – 2002-04). Reproductive Health Index was computed on the basis of five variables such as total fertility rate, infant mortality rate, birth order, delivery care and female educational attainment. Results: In terms of reproductive and child health, a wide range of variation exists in India in its different regions. The study reveals that among Indian states, 13 states have an index value less than the national average. On the basis of the reproductive health index, the Indian states can be divided into three categories, namely; progressive states, semi progressive states and backward states. Conclusions: The interstate differences in healthcare utilization are partly due to variations in the implementation of maternal health care programs as well as differences in availability of and accessibility to healthcare between Indian states.